Translating ENIGMA schizophrenia findings using the regional vulnerability index: Association with cognition, symptoms, and disease trajectory. Issue 1 (28th May 2020) - Kochunov, Peter; Fan, Fengmei; Ryan, Meghann C.; Hatch, Kathryn S.; Tan, Shuping; Jahanshad, Neda; Thompson, Paul M.; van Erp, Theo G. M.; Turner, Jessica A.; Chen, Shuo; Du, Xiaoming; Adhikari, Bhim; et al.
Abstract: Patients with schizophrenia have patterns of brain deficits including reduced cortical thickness, subcortical gray matter volumes, and cerebral white matter integrity. We proposed the regional vulnerability index (RVI) to translate the results of Enhancing Neuro Imaging Genetics Meta‐Analysis studies to the individual level. We calculated RVIs for cortical, subcortical, and white matter measurements and a multimodality RVI. We evaluated RVI as a measure sensitive to schizophrenia‐specific neuroanatomical deficits and symptoms and studied the timeline of deficit formations in: early (≤5 years since diagnosis, N = 45, age = 28.8 ± 8.5); intermediate (6–20 years, N = 30, age 43.3 ± 8.6); and chronic (21+ years, N = 44, age = 52.5 ± 5.2) patients and healthy controls ( N = 76, age = 38.6 ± 12.4). All RVIs were significantly elevated in patients compared to controls, with the multimodal RVI showing the largest effect size, followed by cortical, white matter and subcortical RVIs ( d = 1.57, 1.23, 1.09, and 0.61, all p < 10 −6 ). Multimodal RVI was significantly correlated with multiple cognitive variables including measures of visual learning, working memory and the total score of the MATRICS consensus cognitive battery, and with negative symptoms. The multimodality and white matter RVIs were significantly elevated in the intermediate and chronic versus early diagnosis group, consistent with ongoing progression. Cortical RVI was stable in the three disease‐duration groups, suggesting neurodevelopmental origins of cortical deficits. In summary, neuroanatomical deficits in schizophrenia affect the entire brain; the heterochronicity of their appearance indicates both the neurodevelopmental and progressive nature of this illness. These deficit patterns may be useful for early diagnosis and as quantitative targets for more effective treatment strategies aiming to alter these neuroanatomical deficit patterns. Abstract : We developed the regional vulnerability index (RVI) to quantify individual similarity to the expected schizophrenia deficits patterns derived from large‐scale meta‐analyses performed by Enhancing Neuro Imaging Genetics Meta‐Analysis (ENIGMA) consortium. RVIs for cortical, subcortical, and white matter measurements and a cross‐modality RVI showed significant association with illness duration, cognitive deficits and symptoms. The similarity to expected disorder patterns captured by RVI may be useful for early diagnosis and as quantitative targets for more effective treatment strategies aiming to alter the formation of neuroanatomical deficits.